2005
DOI: 10.1161/01.hyp.0000165025.16381.44
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Pressure Augmentation Predicts Adverse Cardiovascular Events in Patients With Established Coronary Artery Disease

Abstract: Abstract-Pulse pressure (PP), a marker of arterial stiffness, predicts cardiovascular risk. We aimed to determine whether augmentation pressure (AP) derived from the aortic pressure waveform predicts major adverse cardiovascular events (MACE) and death independently of PP in patients with established coronary artery disease (CAD). We prospectively followed-up 297 males undergoing coronary angiography for 1186Ϯ424 days. Ascending aortic pressure tracings obtained during catheterization were used to calculate AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
190
1
21

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(220 citation statements)
references
References 43 publications
8
190
1
21
Order By: Relevance
“…16 An invasive study in male subjects undergoing cardiac catheterization for presumed coronary artery disease related intra-aortic AI to outcome. 32 It may be that in our cohort with a low prevalence (7%) of known vascular disease, other factors including hypertension become more relevant in determining outcome than vascular stiffness. Another possibility in those on hemodialysis is the presence of an arteriovenous fistula, which has been shown to alter arterial hemo- dynamics, and it could be possible that AI measures other factors in addition to central arterial wave reflection in participants with such a large arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 89%
“…16 An invasive study in male subjects undergoing cardiac catheterization for presumed coronary artery disease related intra-aortic AI to outcome. 32 It may be that in our cohort with a low prevalence (7%) of known vascular disease, other factors including hypertension become more relevant in determining outcome than vascular stiffness. Another possibility in those on hemodialysis is the presence of an arteriovenous fistula, which has been shown to alter arterial hemo- dynamics, and it could be possible that AI measures other factors in addition to central arterial wave reflection in participants with such a large arteriovenous fistula.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, the treatment was more effective with subjects who fulfilled the International Diabetes Federation criteria for MS. The result is important, because a 10% elevation in AIx increases the risk of major adverse cardiovascular events by 28% in patients with coronary artery disease and patients with MS are a high-risk group (Chirinos et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, central blood pressure (CBP), reflecting ascending aortic blood pressure, has also been important because its elevation induces coronary atherosclerosis. 3,4 In addition, CBP is thought to reflect direct stress on the heart because it expresses the pressure-loading condition next to the heart compared with peripheral blood pressure. 5,6 The large-scale ASCOT-CAFÉ study 7 reported that CBP may be a determinant of clinical outcomes and that brachial blood pressure is not always a good indicator of a drug's blood pressure-lowering effect on arterial hemodynamics (CAFÉ trial).…”
Section: Introductionmentioning
confidence: 99%